Interview: Ben Lillie on Science and the Storytelling Revival. (7th January 2013) - Linett, Peter
<x xml:space="preserve">Abstract</x> Ben Lillie is the co‐founder and host of the Story Collider, a live storytelling series, podcast, and online magazine devoted to presenting true, personal stories about the effect of science on people's lives. Since 2010, scientists and non‐scientists alike have told stories at events held at bars and other casual venues in Brooklyn and Manhattan, as well as other cities. They can be heard on the Story Collider podcast, available on iTunes and at the organization's website: storycollider.org. Lillie is also a writer and contributing editor at TED. He earned his Ph.D. in high‐energy physics at Stanford University. Peter Linett recently spoke with Lillie about the broader storytelling revival and the changing culture of science communication.